2014
DOI: 10.1186/1471-2180-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus GG restoration of the gliadin induced epithelial barrier disruption: the role of cellular polyamines

Abstract: BackgroundCeliac disease is characterized by enhanced intestinal paracellular permeability due to alterations of function and expression of tight junction (TJ) proteins including ZO-1, Claudin-1 and Occludin. Polyamines are pivotal in the control of intestinal barrier function and are also involved in the regulation of intercellular junction proteins. Different probiotic strains may inhibit gliadin-induced toxic effects and the Lactobacillus rhamnosus GG (L.GG) is effective in the prevention and treatment of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 46 publications
4
53
1
2
Order By: Relevance
“…For example, they can downregulate proinflammatory cytokines by inhibiting proinflammatory nuclear factor jB and increasing expression of cytoprotective heat shock proteins [56], inducing mucosal immunoglobulin A production and providing protection against respiratory influenza virus infection [57], restoration of the gliadin-induced epithelial barrier disruption and enhancing intestinal epithelial integrity [58], and affecting pain perception and gut motility by targeting sensory nerves in the nervous system [59].…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…For example, they can downregulate proinflammatory cytokines by inhibiting proinflammatory nuclear factor jB and increasing expression of cytoprotective heat shock proteins [56], inducing mucosal immunoglobulin A production and providing protection against respiratory influenza virus infection [57], restoration of the gliadin-induced epithelial barrier disruption and enhancing intestinal epithelial integrity [58], and affecting pain perception and gut motility by targeting sensory nerves in the nervous system [59].…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…Indeed, gluten-degrading bacteria have been isolated from the gastrointestinal tracts of humans and pigs (21)(22)(23)(24)(25). Previously, it was shown that Lactobacillus rhamnosus GG improves the intestinal permeability of Caco-2 cells when exposed to gliadin peptides (26). Strains belonging to the Bifidobacterium genus (e.g., Bifidobacterium longum CECT 7347, Bifidobacterium bifidum CECT 7365) decreased the cytotoxic and inflammatory effects of gluten peptides (25,27).…”
mentioning
confidence: 99%
“…Another study demonstrated that the administration of LGG on CaCo-2 cells exposed to gliadin and with an altered permeability is associated to a restoration of barrier function, by acting on ZO-1, Claudin-1 and occludin gene expression. Cellular polyamines are necessary for LGG action on tight junctions [58]. It was proven that LGG ameliorates intestinal epithelial barrier also by inducing human intestinal fibroblasts-responsive proteins production.…”
Section: Bacteria Involved In Mhmentioning
confidence: 99%